Associação de Fusarium solani, Macrophomina phaseolina e Rhizoctonia solani causando podridão radicular em meloeiro sob efeito de adubos verdes - Porto, Maria Alice Formiga (2015)
The occurrence of root diseases is one of the main reasons of yield loss in melon crop, especially the pathogens that causes root and collar rot, as the fungi Fusarium solani (Mart.) Sacc., Macrophomina phaseolina (Tassi) Gold. and Rhizoctonia solani Kuhn, being observed in muskmelon either alone or associated. The use of crop residues and plant materil, besides the improvement in the physical properties of the soil, also favors microbial activity of the species presents in this environment and affects negatively onpathogens population. Therefore, the objective of this work was to evaluate the associations of F. solani, M. phaseolina and R. solani in the incidence and severity of root rot and fresh and dry weight of muskmelon and verify the effect of green manure in root rot caused by these pathogens alone or associated. The experiment was conducted in two stages, in a greenhouse. The first stage evaluated the association of F. solani, M. phaseolina and R. solani causing root rot in melon, using a randomized block design with 8 treatments (F. solani; M. phaseolina, R. solani, F. solani + M. phaseolina, F. solani + R. solani; M. phaseolina + R. solani, F. solani + M. phaseolina + R. solani; non-infested soil) and 8 repetitions with experimental unit of one pot (3.5 L) with 2 plants. The characteristics evaluated were the incidence of root rot in melon plants at the end of the cycle; disease severity based on a scale notes, and the fresh and dry weight of muskmelon. At the second stage, evaluated the effects of green manure in the association of these pathogens in muskmelon, which was conducted one experiment with Jack beans (Canavalia ensiformis L. DC) and another with Pearl millet (Pennisetum glaucum (L.) R. BR.). The experiments were performed simultaneously in a randomized block design with 8 x 4 factorial {8 types of fungi / association (M. phaseolina, R. solani, F. solani, M. phaseolina + R. solani; M. phaseolina + F. solani, R. solani + F. solani; M. phaseolina + R. solani + F. solani; non-infested soil), 4 forms of management [incorporated, in coverage, polyethylene film (mulching) and without managment]} and 4 repetitions. The characteristics evaluated were the incidence of root rot of melon plants at the end of the cycle, and the fresh and dry weight of muskmelon. The results of disease incidence were submitted to the non-parametric test of Kruskal-Wallis and the fresh and dry weight of muskmelon were analyzed by the Scott-Knott test, both with significance level of 5% of probability (α = 0.05%). At stage 1, the treatment with the three pathogens F. solani, M. phaseolina and R. solani associated resulted in lower incidence of plants with symptoms and was not statistically different from the control. The pathogen R. solani was the least prevalent in the associations. The lowest accumulation of fresh and dry matter happened when the soil was infested with Fusarium solani alone. At stage 2, Jack beans in coverage provided lower incidence of root rot in muskmelon with Fusarium solani alone and in triple association (F. solani +M. phaseolina and R. solani). The use of Pearl millet had no effect on root rot incidence in most treatments. In both experiments (Jack beans andPearl millet), Macrophomina phaseolina was the fungus that prevailed in almost all associations. Jack beans and millet did not increase the fresh and dry weight of muskmelon in most treatments